Destructive and non-destructive testing methods for characterization and detection of machining-induced white layer: A review paper. (November 2018) - Brown, M.; Wright, D.; M'Saoubi, R.; McGourlay, J.; Wallis, M.; Mantle, A.; Crawforth, P.; Ghadbeigi, H.
Abstract: The presence of machining-induced white layer in the near-surface of critical aeroengine alloys has a detrimental effect on the lifetime of a component. Present techniques for identifying and characterizing white layer, such as optical microscopy and hardness testing, whilst effective, are destructive, costly and time-consuming. Non-destructive testing methods may, therefore, offer improvements to the process of white layer detection. This paper discusses the formation mechanisms and the defining physical properties of machining-induced white layers before offering a comprehensive review of the current state-of-the-art in both destructive and non-destructive testing methods for detecting this anomalous surface feature.